Monitorization of autonomic stress response of nurse students in hospital clinical simulation (2021)
The aims of this study were to analyze the autonomic stress response of nurse degree students during a hospital clinical simulation and to analyze differences in the autonomic stress response of nurse degree students during a hospital clinical simulation depending on their psychological profile. We analyzed in 45 nurse students their psychological profile (purpose in life, coping flexibility, perceived stress, Framingham Type A Behavior, and personality) and the autonomic modulation by the heart rate variability in a hospital clinical simulation. Students presented decreased heart rate variability and different autonomic stress responses depending on the different psychological parameters evaluated. We concluded that a hospital clinical simulation produced a large sympathetic modulation of nurse students that was maintained during the entire clinical simulation. The autonomic response was modulated by the psychological profile of students, showing higher purpose in life, perceived stress, and neuroticism, presenting higher parasympathetic modulation.